Ochoa syndrome: An overlooked diagnosis - A case report - Mário Nicolau Barros Jacobino; Patrícia Barros Aquino Jacobino; Matheus Saraiva Lopes; Francisco Arisneto Avelino Fontenele Júnior (Archives of Clinical Nephrology - Peertechz Publications, 2023)
The Urofacial Syndrome or Ochoa is a very rare clinical condition, and is unknown by a large part of the medical community; it is characterized by an inverted facial expression, resulting from abnormal contraction of facial and ocular muscles, especially when smiling, in addition to the presence of urinary abnormalities. Patients with this syndrome are at a higher risk of developing urinary incontinence, changes in the bladder, vesicoureteral reflux, hydroureteronephrosis, and predisposition to severe urinary infections, in addition to chronic kidney disease. This article presents a case of a 22-year-old female, resident of Piauí/Brazil, who presented at the age of 5, the first symptoms of the disease mainly related to the urinary tract (such as urinary frequency), in addition to the sign of inverted face, in which the patient presents the inverted smile characteristic of the disease when commanded to smile, associated with nocturnal lagophthalmos. The patient evolved at 12 years of age, with end-stage chronic kidney disease and a need for renal replacement therapy. This is one of the rare cases of the disease, in which the patient presents the complete characteristics of the inverted smile pathology and complications in the urinary tract. The inverted facial expression is an easily recognized sign, and it is a very characteristic finding of the disease, not finding explanations of morphological alterations or lesions. therefore, it is evident that early diagnosis with the institution of appropriate treatment, avoids possible damage to the urinary tract from childhood, allowing better management and quality of life in these patients.